Crystal structure of (tricyclohexylphosphane-κP)-[(Z)-N-(3-fluorophenyl)-O-methylthiocarbamato-k1S]gold(I), C26H40AuFNOPS - Yeo, Chien Ing *; Tan, Yee Seng *; Tiekink, Edward R. T. * (De Gruyter Open, 2021)
C26H40AuFNOPS, triclinic, P1 (no. 1), a = 9.62498(7) Å, b = 11.78239(10) Å, c = 12.74349(13) Å, α = 78.7411(8)°, β = 73.5635(8)°, γ = 76.6096(1)°, V = 1335.34(2) Å3, Z = 2, Rgt(F) = 0.0224, wRref(F2) = 0.0557, T = 100 K.